Analisis Kemampuan Pemahaman Konsep Siswa pada Luas Permukaan Kerucut dengan Pendekatan PBL - Mariana Marta Towe; Kristina Beto Nama (Journal on Education, 2024)
This research aims (1) to determine the steps for learning about the surface area of ​​a cone using the Problem Based Learning (PBL) approach and (2) to describe students' conceptual understanding abilities in the material regarding the surface area of ​​a cone after learning using the PBL approach. This research was conducted at Panca Marga State Middle School in April 2023. This research method is qualitative research. The subjects in this research were 20 class VIII students, and 2 students' work samples were taken. The data collection methods used were Student Worksheets (LKS), documentation, written tests and interviews. Data analysis includes data reduction, data presentation and drawing conclusions. The results of this research show that (1) Learning steps on cone surface area material using the PBL approach are effective in improving students' understanding abilities, namely (a) orienting students to the problem, (b) organizing students' learning, (c) guiding investigations individually and in groups, (d) developing and presenting the results of the work, (e) analyzing and evaluating the solution process, (2) Ability to understand the concepts of class VIII students after following learning with the PBL approach, namely for questions number 1 and 2, 20 students were able to achieve indicators 1-4 understanding concepts, namely presenting concepts as a form of representation, developing necessary and sufficient conditions, using, exploiting and selecting certain procedures, and classifying algorithm concepts for problem solving.